Anisotropy of magnetic susceptibility of Cretaceous to Eocene volcanic rocks from southern part of King George Island, West Antarctica - Jerzy Nawrocki; Tomasz Werner (Polish Polar Research, 2025)
The anisotropy of magnetic susceptibility (AMS) was determined for 147 specimens from 14 sites of Cretaceous to Eocene volcanics from south-central King George Island. For selected specimens parameters of hysteresis and thermomagnetic behavior were also studied. The AMS record was generally not modified by tectonic stress and deformations. In these weakly anisotropic rocks, the maximum susceptibility axes in most cases are convergent with the magma flow directions. The AMS data from the rocks cropping out close to the Ezcurra Fault do not support thesis about large scale dextral tectonic transport along it. The terrane model of this part of King George Island also seems to lack justification. The Ezcurra Fault most probably did not act as the strike-slip fault at least since the late Eocene.